Is there more to compensation than money? The empirical study of dimensionality of the total rewards model and its implications for entrepreneurship - Konrad Kulikowski; Piotr Sedlak (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: We aim to verify the dimensionality of the total rewards (TR) model, the idea that employees' compensations do not consist only of money but encompass all financial and non-financial values that employees received from their work. Research Design & Methods: Drawing inspirations from three influential TR models and using data from a large multi-occupational online survey, we conducted exploratory factor analysis (FA) (n = 3022) to test TR dimensionality and structural equation modelling (SEM) (n = 2641) to test TR validity. Findings: The FA results revealed the two-dimensional structure of TR as best fitting to data, showing financial (tangible) and non-financial (intangible) rewards as two distinct aspects of compensation. The SEM analysis showed specific patterns of associations for each TR dimension with employee loyalty, motivation, intention to quit, and organizational performance. Implications & Recommendations: The success of an entrepreneurial firm might depend not only on innovation in products and services but also on innovative compensation that allows for gaining competitive advantages. The TR model might be used to address these challenges and build a competitive workforce by attracting talented employees from the labour market even under financial resources scarcity. Contribution & Value Added: By showing the role of intangible rewards in compensations, our findings might inspire further entrepreneurial research and provide entrepreneurial firms with the conceptual device to design compensation systems that accumulate human capital not only by money but also via intangible rewards.
Keywords: J33; J32; M52; 330; factor analysis; intangible; Pay; Rewards; SEM; total rewards